If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 5) + -2(x + 4) = -3(x + 3) + -4(x + 4) Reorder the terms: -5(5 + x) + -2(x + 4) = -3(x + 3) + -4(x + 4) (5 * -5 + x * -5) + -2(x + 4) = -3(x + 3) + -4(x + 4) (-25 + -5x) + -2(x + 4) = -3(x + 3) + -4(x + 4) Reorder the terms: -25 + -5x + -2(4 + x) = -3(x + 3) + -4(x + 4) -25 + -5x + (4 * -2 + x * -2) = -3(x + 3) + -4(x + 4) -25 + -5x + (-8 + -2x) = -3(x + 3) + -4(x + 4) Reorder the terms: -25 + -8 + -5x + -2x = -3(x + 3) + -4(x + 4) Combine like terms: -25 + -8 = -33 -33 + -5x + -2x = -3(x + 3) + -4(x + 4) Combine like terms: -5x + -2x = -7x -33 + -7x = -3(x + 3) + -4(x + 4) Reorder the terms: -33 + -7x = -3(3 + x) + -4(x + 4) -33 + -7x = (3 * -3 + x * -3) + -4(x + 4) -33 + -7x = (-9 + -3x) + -4(x + 4) Reorder the terms: -33 + -7x = -9 + -3x + -4(4 + x) -33 + -7x = -9 + -3x + (4 * -4 + x * -4) -33 + -7x = -9 + -3x + (-16 + -4x) Reorder the terms: -33 + -7x = -9 + -16 + -3x + -4x Combine like terms: -9 + -16 = -25 -33 + -7x = -25 + -3x + -4x Combine like terms: -3x + -4x = -7x -33 + -7x = -25 + -7x Add '7x' to each side of the equation. -33 + -7x + 7x = -25 + -7x + 7x Combine like terms: -7x + 7x = 0 -33 + 0 = -25 + -7x + 7x -33 = -25 + -7x + 7x Combine like terms: -7x + 7x = 0 -33 = -25 + 0 -33 = -25 Solving -33 = -25 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(3x-1)+2=3(x+2)-6 | | 1x^2+14x+48=0 | | -3(m+6)=-42 | | -6(x-8)+7=55 | | .5+3x=-9x-2 | | -6+x-8x-12=-15 | | .5+3x=-9-2 | | 11.99(1+p)=47.96 | | ln(x)=11.43 | | 750=12.5x+300 | | 750=12.5+300 | | 5x-10+6=2x+8 | | (-4)+2+4+1= | | log(3)*8+log(3)*x=3 | | 5(y-9)=60 | | 2x-7=-8 | | 155=90+n | | 12+2x=36 | | 9m+4n-6m+9m= | | t^3+2t^2-1=0 | | y=0.4x^5+-2x^4+x^3+-0.5x+3 | | 5(2x-8)=4x+2 | | 5x=9-2y | | 6*40=136 | | 12x+28=-6x+-8 | | 2X+20=3X+120 | | 6(w+5)= | | -3b-4=-4b-3b | | 75=30y+15 | | f(x)=.4x^5-2x^4+x^3-.5x+3 | | 4b+16a= | | 10x+11=3x-10 |